Citizen Journalism, Information Disorder, and Democratic Stability in Nigeria - Chinyere Igwe Ordu (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2026)
The rapid expansion of digital technologies and social media platforms has transformed the landscape of news production and dissemination in Nigeria, giving rise to the increasing prominence of citizen journalism. Citizen journalism enables ordinary individuals to gather, produce, and distribute news content outside the traditional structures of professional media institutions. While this development has broadened public participation in information sharing and democratic discourse, it has simultaneously intensified the challenge of information disorder, including misinformation, disinformation, and malinformation. In the Nigerian context, where political tensions, ethno-religious sensitivities, and weak information verification systems often intersect, the proliferation of unverified citizen-generated content has significant implications for democratic stability. This paper examines the relationship between citizen journalism, information disorder, and democratic stability in Nigeria. It explores how the accessibility of smartphones, social networking platforms, and digital communication tools has empowered citizens to act as alternative information providers, especially during political events, elections, and crises. However, the absence of professional gatekeeping, editorial oversight, and fact-checking mechanisms frequently leads to the rapid circulation of inaccurate or manipulated information. Such information disorder can influence public perception, deepen political polarization, incite social tensions, and undermine trust in democratic institutions. The paper adopted secondary data to interrogates the dual role of citizen journalism as both a facilitator of participatory democracy and a potential driver of information instability. The paper argues that while citizen journalism has enhanced media pluralism and accountability, its unregulated nature poses risks to democratic processes when misinformation spreads unchecked. The paper concludes by emphasizing the need for stronger media literacy, ethical digital practices, collaborative fact-checking initiatives, and policy frameworks that promote responsible citizen participation in the digital information ecosystem.